Water-use characteristics of Palmiet (Prionium serratum), an endemic South African wetland plant - AJ Rebelo; C Jarmain; KJ Esler; RM Cowling; DC Le Maitre (Water SA, 2020)
Palmiet, Prionium serratum, is an endemic wetland plant which dominates oligotrophic wetlands throughout the Cape Floristic Region, South Africa. Palmiet is often perceived as undesirable by landowners, in part because it is thought to have high water-use, although little is known about the water-use of this important wetland species. We estimated the water-use dynamics of Palmiet at the leaf scale, using stomatal conductance measurements, and at the wetland scale, by modelling evapotranspiration using remote sensing and an energy-balance model. Factors that influenced Palmiet water-use were also considered, and seasonal variations were analysed. The aim was to estimate Palmiet wetland water-use, and to develop a set of crop factors (Kc) for use in hydrological modelling of catchments containing Palmiet wetlands. Results show that Palmiet has a comparatively low stomatal conductance (11–152 mmol∙m-2∙s-1), which was lower in summer than winter, and moderate evapotranspiration for a riparian species (1 220 mm∙a-1 compared to a local reference evapotranspiration of 1 302 mm∙a-1 and A-Pan evaporation of 2 809 mm∙a-1), which was higher in summer (more energy to drive evapotranspiration and higher vapour pressure deficits). Morphological and physiological adaptations to nutrient poverty or periodic drought are suggested theories which may explain the controls on transpiration for Palmiet.